Incidence rates and case fatality rates of portal vein thrombosis and Budd-Chiari Syndrome - Ageno, Walter; Dentali, Francesco; Pomero, Fulvio; Fenoglio, Luigi; Squizzato, Alessandro; Pagani, Giovanni; Re, Roberta; Bonzini, Matteo (Thrombosis and Haemostasis, 2017)
Little information is available on the incidence of splanchnic vein thrombosis and on mortality rates during the acute phase of the disease. We performed a large epidemiologic study on hospital admissions for portal vein thrombosis (PVT) and the Budd-Chiari syndrome (BCS) between 2002 and 2012 in Northwestern Italy. Primary and secondary discharge diagnoses of PVT and BCS were identified using the 9th edition International Classification of Diseases codes 453.0, 572.1 and 452. Hospitalisations for recurrent events were not included. Information was collected on age and gender, vital status at discharge, duration of hospitalisation, and up to five secondary discharge diagnoses. Comorbidity was evaluated using the Charlson comorbidity index (CCI). A total of 3535 patients with PVT and 287 with BCS were hospitalized. The overall gender-specific incidence rates for PVT were 3.78 per 100,000 inhabitants in males and 1.73 per 100,000 inhabitants in females; for BCS 2.0 and 2.2 per million inhabitants, respectively. In-hospital case fatality was 7.3 % in patients with PVT and 4.9 % in patients with BCS. Age, non-abdominal solid cancer, and CCI were independently associated with in-hospital mortality in both PVT and BCS after stepwise regression analysis, male gender and haematologic cancer were associated with mortality in BCS patients only. In this large study we confirmed the low incidence of BCS and we found an incidence of PVT higher than previously reported. This incidence was stable during the period of observation. In-hospital mortality is not negligible, in particular in PVT patients.
Keywords: Portal vein thrombosis; Budd-Chiari syndrome; epidemiology; mortality